MEMBINA UKHUWAH ISLAMIYAH BERDASARKAN PETUNJUK ALQURAN - marhaban marhaban (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
Muslim communities know the term ukhuwah Islamiyah. This term need to interpreted, so that our language does not experience confusion. For this reason, a linguistic review needed first to establish the position of the word Islamiyah in the above terms. During this time there was an impression the term mean "brotherhood woven among fellow Muslims" or in other words "brotherhood between Muslims", so that the word Islamiyah was used as the perpetrator of ukhuwah. Ukhuwah which is clearly stated by the al-Quran a Muslim brother, and the brotherhood that is interwoven is not due to religion. This is clearly reflected in the fabric of brotherhood not because of religion.